The uneven geographies of post-political planning: Objections to urban regeneration projects in peripheral and central Israeli cities. (June 2019) - Margalit, Talia; Kemp, Adriana
This article probes the Israeli 'Clearance and Construction' urban regeneration programme, which encourages apartment owners nationwide to turn their old dwellings into new tower-clusters. By comparing distinct planning communications on such projects, we aim to contribute a class-related perspective to the debate on post-politics in planning. Planning literature addresses the neutralizing effects of the neoliberal ethos on urban regeneration, highlighting the techniques through which planners dismiss community needs, use values and local voices. We respond to scholars calling for more nuanced perspectives by analysing a dataset of objection hearings in different cities, tracing how planners present their decisions and advance projects, and how different social groups accept and/or reject planners' rationale. Our findings point to two main outcomes: first, we show that most participants accept the entrepreneurial rationale but their discourse often mixes acceptance with dissent; second, we show that such mixed discourses vary across locations and reflect socio-spatial distinctions. The more affluent participants objected more and highlighted use values and the public interest, yet their discourse largely echoed planners' discourses. Conversely, the poorer objectors, who focused on exchange values, disrupted the consensual planning order by highlighting their own hopes and personal struggles. Who, then, were more submissive to neoliberal ethos? These results, we argue, call for a nuanced analysis of current planning relations. We argue that such analysis should specifically look at synchronization between consensual planning and co-optation, dissent and socio-spatial deviation.